2015
DOI: 10.1109/jmems.2015.2432054
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Stroke 3DOF Stage With Integrated Feedback in MEMS

Abstract: In this paper, we design, fabricate, and validate a large-stroke 3-degree-of-freedom (DOF) positioning stage with integrated displacement sensors for feedback control in a single-mask microelectromechanical systems (MEMS) fabrication process. Three equal shuttles exactly define the position of the stage in x, y, and R z . The kinematic relation between the shuttle positions and the stage position is given by the geometric transfer function. By increasing the order of this geometric transfer function, the stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…While the microactuators with complex driving structures can realize multi-axis motion with large output capability. However, many studies have shown that the reliability in motion behavior of MEMS movable devices with complex structures is a serious challenge, especially in precise control and manufacturing process [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…While the microactuators with complex driving structures can realize multi-axis motion with large output capability. However, many studies have shown that the reliability in motion behavior of MEMS movable devices with complex structures is a serious challenge, especially in precise control and manufacturing process [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%